A CF4 plasma functionalized polypropylene separator for dendrite-free lithium metal anodes. Issue 14 (20th March 2023) - Cao, Shengling; He, Xin; Chen, Manlin; Han, Yu; Wang, Kangli; Jiang, Kai; Zhou, Min
Abstract : A simple and effective plasma functionalization technique for grafting fluorine-containing functional groups on commercial PP separators to induce the formation of LiF-rich SEI films has been proposed. Abstract : Lithium metal is recognized as a promising anode material for next-generation high-energy-density batteries, but uncontrollable lithium dendrites inhibit their further applications. In this paper, fluorine-containing functional groups were grafted on a commercial polypropylene (PP) separator by a simple and efficient plasma functionalization technique. The grafted polar groups enhance the affinity of the PP separator for Li-ions, thus resulting in improved wettability and ion conductivity as well as an enhanced lithium-ion transference number of the separator. Moreover, the introduced fluorine-containing functional groups participate in the formation of a LiF-rich solid electrolyte interface (SEI) film, which regulates the uniform deposition of lithium ions and inhibits lithium dendrite growth. As a result, Li‖Li symmetric batteries equipped with fluorinated PP separators exhibit a long lifespan of nearly 7000 h (1 mA cm −2, 1 mA h cm −2 ) with a low overpotential of 48 mV. This work introduces a simple method to induce the formation of a LiF-rich SEI film, which can be extended to a variety of energy storage systems and provides new routes for the construction of high-performance energy storage technologies.